Revision of the New World Ceratoculicoides Wirth & Ratanaworabhan (Diptera, Ceratopogonidae, Ceratopogonini) - Fasbender, Andrew (European Journal of Taxonomy, 2023)
The New World species of the genus Ceratoculicoides Wirth & Ratanaworabhan are described, illustrated and keyed in both sexes. Ceratoculicoides borkenti sp. nov., C. confusus sp. nov., C. grogani sp. nov., C. pacificus sp. nov. and C. propinquus sp. nov. are described, with C. confusus being the first record of the genus from South America (Colombia). Ceratoculicoides blantoni is a junior synonym of C. virginianus and the identity of C. longipennis remains unclear as the male morphospecies associated in taxonomic literature with the female type series is not conspecific. A morphological phylogeny of all extant species in the genus is presented and characters discussed. The moravicus species group is recognized for a clade of species with the lateral margins of the aedeagus straight or concave.